(untitled) (American Journal of Islam and Society, 2015)
The self-proclaimed Islamic State of Iraq and Syria’s (ISIS) burning to death of Jordanian pilot Moaz al-Kasasba and beheading of twenty-one Egyptians in Libya are just the latest incidents in a series of escalating acts of violence that epitomize the seemingly senseless carnage that so often results from the political radicalization of individual Muslims. As the international media zeroes in on such instances, one often struggles to make sense of the perpetrators’ true motives. But understanding the circumstances that lead up to such viciousness is key if governments are to minimize such acts in the future. What motivates an individual to join a terrorist organization? Is it ideology, politics, poverty, or something else? What might be done to de-radicalize an individual who has joined a terrorist group? The reality is that there is no single pathway toward radicalization. In a May 2010 report entitled “Why Youth Join al-Qaeda,”1 U.S. Army Colonel Matt Venhaus suggested that those seeking to join jihadist networks can be divided into revenge seekers needing an outlet for their frustration, status seekers needing recognition, identity seekers in need of a group to join, and thrill seekers looking for adventure.2 Clearly the motives for terrorism are differentiated and complex, as opposed to uniform and simple. Thus identifying an overarching pattern to understanding how individuals might become susceptible to terrorist recruiters and what intervention strategies can be employed to stop it becomes a very difficult task ...